2010
DOI: 10.5483/bmbrep.2010.43.1.017
|View full text |Cite
|
Sign up to set email alerts
|

KBTBD7, a novel human BTB-kelch protein, activates transcriptional activities of SRE and AP-1

Abstract: In this study, a novel member of BTB-kelch proteins, named KBTBD7, was cloned from a human embryonic heart cDNA library. The cDNA of KBTBD7 is 3,008 bp long and encodes a protein product of 684 amino acids (77.2 kD). This protein is highly conserved in evolution across different species. Western blot analysis indicates that a 77 kD protein specific for KBTBD7 is wildly expressed in all embryonic tissues examined. In COS-7 cells, KBTBD7 proteins are localized to the cytoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The BTB/POZ domain is a highly conserved structural motif involved in transcriptional regulation (Aravind and Koonin, ; Collins et al. , ; Hu et al , ). To test the activation of the transcription function of GmBTB/POZ, we performed a transient expression assay in yeast cells using a GAL4‐responsive reporter system.…”
Section: Resultsmentioning
confidence: 99%
“…The BTB/POZ domain is a highly conserved structural motif involved in transcriptional regulation (Aravind and Koonin, ; Collins et al. , ; Hu et al , ). To test the activation of the transcription function of GmBTB/POZ, we performed a transient expression assay in yeast cells using a GAL4‐responsive reporter system.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that KBTBD6/7 can mediate ubiquitylation and subsequent proteasomal degradation of T-lymphoma and metastasis gene 1 (TIAM1) through binding cullin 3 (CUL3) to form a heterodimeric Cullin-RING ligases comprising CUL3 (CRL3) complex 30 . KBTBD7 directly or indirectly positively regulates the MAPK signaling pathway through activating SRE and AP-1-mediated transcriptional activation 31 . However, the role of KBTBD7 in cardiovascular diseases remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…transcriptional activity when transfected with the control plasmid pCMV-BD encoding the GAL4-DBD alone. LexA-VP16, which can directly activate the expression of the luciferase reporter gene, was used as a positive control (16). When cotransfecting with pL8G5-luc plasmid, the GAL4-ZNF424 fusion protein inhibited luciferase activity by approximately 30% (Fig.…”
Section: Znf424 Functions As a Potential Transcriptional Repressormentioning
confidence: 99%